Resprouters Versus Reseeders: Are Wild Rooibos Ecotypes Genetically Distinct? - Brooks, J.; Makunga, N. P.; Hull, K. L.; Brink-Hull, M.; Malgas, R.; Roodt-Wilding, R. (Frontiers in Genetics, 2021)
Aspalathus linearis (Burm. F.) R. Dahlgren (Fabaceae) or rooibos, is a strict endemic fynbos species, limited to areas of the Cederberg (Western Cape) and the southern Bokkeveld plateau (Northern Cape) in the greater Cape Floristic Region (CFR) of South Africa. Wild rooibos, unlike the cultivated type, is variable in morphology, biochemistry, ecology and genetics. These ecotypes are broadly distinguished into two main groups, namely, reseeders and resprouters, based on their fire-survival strategy. This study aimed to test the hypothesis that wild rooibos ecotypes are distinct in genetic variability and that the ecotypes found in the Northern Cape are distinct from those in the Cederberg. Phylogeographical analysis of both chloroplast (trnLF intergenic region) and newly developed species-specific nuclear markers (microsatellites) was performed on six geographically representative wild rooibos populations. From the diversity indices, it was evident that the wild rooibos populations have low-to-moderate genetic diversity. The Jamaka population (Cederberg, Western Cape) had the lowest haplotype diversity (0.286), and the lowest nucleotide diversity (0.006) even though the data revealed large variations in haplotype diversity (h = 0.286 - 0.900) and nucleotide diversity (π = 0.006 - 0.025) between populations and amongst regions where wild rooibos populations are found. Our data suggests that populations of rooibos become less diverse from the Melkkraal population (Suid Bokkeveld, Northern Cape) down towards the Cederberg (Western Cape) populations, possibly indicative of clinal variation. The largest genetic differentiation was between Heuningvlei (Cederberg, Western Cape) and Jamaka (FST = 0.101) localities within the Cederberg mountainous region, and, Blomfontein (Northern Cape) and Jamaka (Cederberg) (FST = 0.101). There was also a significant correlation between geographical distance and genetic distance (R2 = 0.296, P = 0.044). The presence of three main clusters is also clearly reflected in the discriminant analysis of principal components (DAPC) based on the microsatellite markers. The correct and appropriate management of wild genetic resources of the species is urgently needed, considering that the Cederberg populations are genetically distinct from the Northern Cape wild plants and are delineated in accordance with ecological functional traits of reseeding or resprouting, respectively.